Study of MgO-activated slag as a cementless material for sustainable spray-based 3D printing - Lu, Bing (2021)
3D concrete printing technology greatly facilitates automation in construction which enhances efficiency, productivity and sustainability. This study develops a slag-based mixture as a cementless material for sustainable spray-based 3D printing. Effects of MgO and fly ash cenosphere (FAC) addition on setting, hydration and rheological properties of fresh mixtures are investigated to obtain the optimal mixture. Results show that inclusion of MgO effectively reduces initial setting time of the fresh mixtures. With 40 wt% of GGBS replaced by MgO, initial setting time is greatly reduced from 305 min to 67 min (78% reduction). Fourier-Transformed Infrared (FTIR) spectra suggest the acceleration is plausibly due to the physical aspects. Furthermore, the FTIR spectra show that MgO can effectively activate the slag and also improve water retention. Rheological tests reveal that FAC addition generally reduces dynamic yield stress and plastic viscosity while increases static yield stress of the fresh mixtures, resulting in lower pumping pressures and higher critical ratios. The mixture with 20 wt%/40 wt% FAC addition has 29%/31% lower pumping pressure and 78%/68% higher critical ratio compared with plain MgO-activated slag material, respectively. Hence, the material with tailored rheology leads to better delivery and deposition performance of the mixture and overall spray-printing quality. An optimal mixture was finally selected based on setting, hydration, rheological properties and spray performance. The developed cementless mixture was successfully applied in the vertical spray-based 3D printing of filament and profile, which confirmed its feasibility in engineering applications.